Moisture and Temperature Influence on Thermal Properties of Winged Bean (Psophocarpus tetragonolobus) Seed Accessions - Oriola, K. O.; Hussein, J. B.; Oke, M. O.; Isiaka, R. D. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
The thermal properties of three winged bean seed accessions (Entry 4 Tropical Psophocarpus tetragonolobus (TPT) 6, Entry II Tropical Psophocarpus tetragonolobus (TPT) 30, and Entry 12 Tropical Psophocarpus tetragonolobus (TPT) 32) at 5, 10, 15, 20, and 25% moisture contents and 30, 40, and 50 ᵒC temperatures were determined with the KD2 Pro Thermal Analyzer. The results showed that the thermal properties of the seed accessions were moisture-temperature dependent. Entry II TPT 30 had the highest specific heat capacity (1.37-2.59 kJ.kg-1K-1), while Entry 4 TPT 6 had the highest thermal conductivity (0.17-0.60 W.m-1K-1) and thermal diffusivity (0.19-0.77 x 10-7 m2.s-1) as the temperature and moisture increased. A second-order polynomial model described the relationship between the moisture, temperature, and the three thermal properties studied. Respective high correlation coefficients (R2 ≥ 0.9126, 0.9872, and 0.9801 for Entry 4 TPT 6, Entry II TPT 30, and Entry 12 TPT 32 accessions, respectively) indicated their ability to simulate these parameters within the moisture-temperature domain studied. The winged bean seeds’ thermal properties will be used to guide design decisions for the creation of agricultural machinery, thermal processes, and equipment required for storage, drying, heating, and cooling.